REALIZATION OF PRINCIPLES ORGANIZATIONAL - TECHNICAL DESIGNING OF ROBOTIZED COMPLEXES - U.G. LUDMIRSKIY; М.V. SOLTOVETS; A.N. GRITSYNA (Advanced Engineering Research)
We present the experience of developing weld technological complexes, applying the principles of organizational and technological design. We consider organization, technology and equipment of workshops for welding rotary harvester header cylinders.